2016
DOI: 10.1136/bmjgast-2016-000080
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota associated with HIV infection is significantly enriched in bacteria tolerant to oxygen

Abstract: ObjectivesGut microbiota modifications occurring during HIV infection have recently been associated with inflammation and microbial translocation. However, discrepancies between studies justified a comprehensive analysis performed on a large sample size.Design and methodsIn a case–control study, next-generation sequencing of the 16S rRNA gene was applied to the faecal microbiota of 31 HIV-infected patients, of whom 18 were treated with antiretroviral treatment (ART), compared with 27 healthy controls. 21 sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
65
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 55 publications
12
65
3
Order By: Relevance
“…Our result is consistent with most of published studies which reported Proteobacteria were more abundant in HIVinfected individuals although others reported no change [10,11,[25][26][27][28][29][30]. The phylum Fusobacteria (most driven by its constituent genus Fusobacterium) which was reported associated with intestinal in ammation [31,32] and enriched in HIV-infected individuals in some studies [26,30,33,34]. Here, we found Fusobacterium enriched in IR and INR group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result is consistent with most of published studies which reported Proteobacteria were more abundant in HIVinfected individuals although others reported no change [10,11,[25][26][27][28][29][30]. The phylum Fusobacteria (most driven by its constituent genus Fusobacterium) which was reported associated with intestinal in ammation [31,32] and enriched in HIV-infected individuals in some studies [26,30,33,34]. Here, we found Fusobacterium enriched in IR and INR group.…”
Section: Discussionsupporting
confidence: 92%
“…The phylum Bacteroidetes which include the families Bacteroidaceae, Prevotellaceae, Porphyromonadaceae, and Rikenellaceae, exhibited a more heterogeneous pattern of changes in HIVinfected individuals [10,11,22,[25][26][27][28][29][30][33][34][35][36][37]. The family Bacteroidaceae (mostly driven by the abundance of the genus Bacteroides) is generally considered to play an anti-in ammatory role [38][39][40][41], were depleted in IR and INR group.…”
Section: Discussionmentioning
confidence: 99%
“…Taxa from bacterial phyla Proteobacteria, Fusobacteria and Bacteroidetes have been reported different between HIV positive and negative individuals in studies. Our result was consistent with most of published studies which reported that Proteobacteria were more abundant in HIV-infected individuals although others reported no change [8,[10][11][12][28][29][30][31][32][33]. The family Enterobacteriaceae has been reported positively associated with markers of monocyte activation (sCD14), in ammation and colonic T cell activation and inversely correlated with blood CD4+ T cell counts [30,32,34].…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress in the gastrointestinal tract (GIT) is thus closely linked to dysbiosis during IBD and non-IBD gut disorders and might be an important therapeutic target. 6,7 Another key contributor to dysbiosis and mucosal barrier impairment during IBD is a deficiency in the secretion of antimicrobial proteins (AMPs) such as defensins, cathelicidins, and C-type lectins resulting notably from Paneth cell dysfunction. 8 This enteric arsenal forms part of innate immunity, contributing to a balanced clearance of pathogens and tolerance of commensal microbes in the gut.…”
Section: Background and Aimsmentioning
confidence: 99%